Venezuela in the estertors of the spanish domain and its relationship with the Foreign Antilles, 1820-1823 - Pita Pico, Roger (2021)
The central axis of this article aims to address the relationship of the Spanish political and military authorities settled in Venezuela with the foreign colonies in the Caribbean in the culminating stage of the independence struggle. Under the atmosphere of tension and uncertainty due to the war, the diplomatic deployment of the Spanish government based in Venezuela was key, not only in its rapprochement with the governments of those islands but with the powers on which they depend. Even with all the difficulties, the aid of these foreign colonies to the agonizing government of Venezuela was valuable, although it was not enough to prevent it from succumbing to the offensive of the republican government, which increasingly resorted to the political, economic and military support of island possessions in the Caribbean.